Modeling Of Gear Mechanism Using Transient Finite Element Method - F. R. M., Romlay; Wan Azhar, Wan Yusoff (2006)
This paper presents a dynamic analysis of gear model using Finite Element Method (FEM) via transient characteristic. Traditionally, the stress analysis is done separately with dynamic properties due to limitation of complex equation and error control. A FEM analyst is carrying out to formulate and solve large systems of algebraic equations to obtain the relationship between the contact parameter and the kinematics function. The loading conditions are chosen due to affects of gear mechanism which can influence the gear transmission. Therefore, model analysis for gear mechanism is obtained to investigate the stress distribution on real time by transient FEM. From the transient FEM results, the analysis has to determine which contacts occur at each stage of the work cycle, to derive the resulting kinematics functions, and to identify qualitative kinematics variations due to contact changes in time-step domain. The results from the simulation are in good agreement comparing with the theory calculation.